Endometrioma is a Responsible Factor for Reduced Ovarian Reserve (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): The aim of the study was to assess ovarian reserve (OR) of patients with endometrioma and to explore the differences of ovarian reserve in age matched group of infertile patients without endometrioma.Materials and methods: This prospective analytic study was done in Infertility Care and Research Center, between January 2013 and December 2015 to assess the ovarian reserve of patients with endometrioma. During this period 105 patients of endometriosis with endometrioma were selected for study. Selection criteria were: no history of previous surgery,